Prostorska razporeditev gozdov na območju Ljubljane v prihodnosti - Kutnar, Lado (Gozdarski vestnik, 2010)
The redistribution of forest vegetation types in Ljubljana region, driven by the expected climate change, has been simulated. According to three climate scenarios, following the model the decrease of the actual prevailing mesic beech forest share could be expected. In a warmer climate, predicted by all three future scenarios, different thermophilous forests might expand over a larger area of the country.
Keywords: gozdovi; Ljubljana; prostorska razporeditev; podnebne spremembe; gozdna vegetacija; modeli; simulacija